Effects of variations on slopes of yield and average kinetic energy curves as a function of fragment mass on standard deviation of final kinetic energy distribution from thermal neutron induced fission of U-235 - Montoya, Modesto (2007)
The mass and kinetic energy distributions of fragments from thermal neutron induced fission of U-233 have been studied using a Monte-Carlo simulation. In our previous work [1] we reproduce the two pronounced broadenings in the standard deviation (SD) of the kinetic energy distribution of the final fragment at mass number around m=109, and m=125, respectively, which is agreement with the experimental data obtained by Belhafaf et al. [2].